A Comparitive Study of CNC Milling Cutting Path Strategies - Khleif, Ali Abbar; Nemat, Majeed; Khniefer, Hasan Nemah (Al-Nahrain Journal for Engineering Sciences, 2017)
This paper investigates the effect of cutter path used in the milling process on the produced surface roughness using two different tools. The cutting paths which are named as; one directional, zigzag , Morph, overlap spiral and spiral are considered as cutter path strategies. The cutter path strategies greatly influenc the surface finish of the work pieces. The objective of this study is to investigate the best cutting characteristics and effects of cutting path for aluminuim using end mill and ball mill tools. MASTER CAM software has been used in design and producing NC CODE. The results indicate that the raw tool path strategy and flat end mill tool gives minimum roughness value with (0.15µm), while the spiral tool path strategy and ball end mill tool gives minimum roughness value with (0.76µm).